PENGARUH PELATIHAN DAN TURNOVER INTENTION TERHADAP KINERJA PEGAWAI PADA BAGIAN KEPERAWATAN RSUD LEUWILIANG KABUPATEN BOGOR - Wajihudin; Ahmad Nazir (Al Hasanah Barokah Foundation, 2025)
The purpose of this study was to determine the effect of Training and Turnover Intention on Employee Performance in the Nursing Department of Leuwiliang Hospital, Bogor district, partially or simultaneously. The method used is quantitative. The sampling technique used in this study was the slovin method with a total sample of 185 employees from a population of 343 employees. Data collection techniques used observation, interviews and questionnaires. The analytical method uses the validity test method, reliability test, classic assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, hypothesis testing. The results showed that there was a positive and significant influence between Training (X1) and Tunover Intention (X2) on Employee Performance (Y) at Leuwiliang Hospital, Bogor Regency, namely Y = 8.368 + 0.666 X1 + 0.423 X2. From these results it can be concluded that there is a positive relationship between Training (X1) and Turnover Intention (X2) on Performance (Y) in Leuwiliang Hospital, Bogor Regency. And Correlation Coefficient Value Correlation value R = 0.640, meaning that Training (X1) and Turnover Intention (X2) have a very strong level of relationship to employee performance (Y). Determination Value R Square = 0.410, it can be concluded that Training (X1) and Turnover Intention (X2) contribute 41% to employee performance (Y) and the remaining 59% is influenced by other factors. Obtained from the results of the hypothesis test it is explained that the Fcount value is 63.277 > Ftable 3.04 or the probability Sig 0.000 <0.05 then H0 is rejected and Ha is accepted meaning that there is a joint effect between training (X1) and turnover intention (X2) on performance (Y) in Leuwiliang Hospital, Bogor Regency.